Heterologous Immunization with Improved HIV-1 Subtype C Vaccines Elicit Autologous Tier 2 Neutralizing Antibodies with Rapid Viral Replication Control After SHIV Challenge - Gerald K. Chege; Rosamund E. Chapman; Alana T. Keyser; Craig H. Adams; Kealan Benn; Michiel T. van Diepen; Nicola Douglass; Bronwen Lambson; Tandile Hermanus; Penny L. Moore; Anna-Lise Williamson (Viruses)
We previously reported on HIV vaccines that elicited autologous Tier 2 neutralizing antibodies (nAbs) in rabbits. In the current study, we sought to establish a proof of concept that HIV vaccines using identical designs elicit Tier 2 nAbs in arhesus macaque (RM) model. DNA and MVA vaccines expressing SIV Gag and HIV-1 Env antigens were constructed, and in vitro expression was confirmed. A soluble envelope protein (gp140 Env) was expressed from a stable HEK293 cell line and purified using lectin affinity and size exclusion chromatography. The expression and secretion of SIV Gag and HIV-1 Env by the DNA and MVA vaccines was verified in vitro. Five RMs were inoculated with two DNA, followed by two MVA, and finally with two gp140 Env vaccines at weeks 0, 4, 8, 12, 20 and 28. Vaccine-induced T cell immunity was measured by IFN-γ ELISpot while nAbs were evaluated against MW965 (Tier 1A), 6644 (Tier 1B), autologous ZM109.5A and a closely-related ZM109.B4 (Tier 2) pseudovirions. Vaccinated RMs were challenged intrarectally with simian-human immunodeficiency virus (SHIV), four weeks after the final vaccination, as was an unvaccinated control group (n = 4). Following vaccination, all the animals developed moderate IFN-γ ELISpot responses after the DNA vaccinations which were boosted by the MVA vaccine. After the gp140 Env boost, all animals developed nAbs with peak median titres at 762 (MW965) and 263 (ZM109.5A). The vaccinated animals became infected after a similar number of challenges to the unvaccinated controls, and the resultant number of viral copies in the blood and the lymphoid tissues were similar. However, the duration of detectable viraemia in the vaccinated animals (median: 2 weeks) was shorter than the controls (median: 8.5 weeks). These data show that the vaccines elicited robust cellular and functional humoral immune responses that resulted in a quicker control of viraemia.